Understanding purchase decision for remanufactured laptops: A utility-based analysis of consumer preferences in an emerging economy - Komang Nickita Sari; Maria Anityasari; Tatbita Titin Suhariyanto; Rindi Kusumawardani (Universitas Serang Raya, 2026)
This study investigates the determinants of consumers’ purchase decisions for remanufactured laptops in Indonesia, where a limited understanding of remanufacturing continues to hinder adoption of the circular economy. Rather than examining purchase intention, the study model’s purchase decision as a trade-off-based decision process reflects consumers’ decision-making of remanufactured products. A MaxDiff (Best–Worst Scaling Case 1) discrete choice experiment was conducted involving 434 Indonesian undergraduate students. Preferences were modeled within a random utility theory framework using multinomial logit estimation via maximum likelihood, and consumer heterogeneity was subsequently examined through latent class analysis, revealing four distinct preference segments. The results show that the dominant driver of purchase decision is functionality expectation, followed by perceived consumer effectiveness and perceived safety, indicating that consumers prioritize performance assurance and risk reduction over environmental motivations. Environmental consciousness and social influence have weaker effects, indicating an attitude–behavior gap for sustainable consumption. Furthermore, the latent class analysis identified four heterogeneous consumer segments with varying valuation logics. This suggests practical implications for future strategies to increase the purchase decision of remanufactured electronics in emerging economies through knowledge creation about the customer perceptions, where a greater emphasis on functional reliability, certification, and transparent quality communication may prove more effective than traditional environmental appeals.